P2_2 Up Physics - Dangerfield, Kyle; Walton, Samuel; Lewis, Elspeth; Byrne, Jamie (Physics Special Topics, 2017)
The Disney Pixar motion picture Up, features a scene where a house is lifted from the ground by large number of balloons. We used the assumption that the house weighs 45400 kg (100000 lbs), and was lifted by spherical, helium-filled party balloons each with a radius of 0.152 m. The calculated number of balloons required for the house to be uprooted from concrete foundations with a tensile strength in the range 2.2-4.1 MPa, would be between 5.01x10^9 and 9.33x10^9.